Analisis Intensitas Kebisingan Terhadap Pendengaran Pekerja Pabrik Kelapa Sawit PT. Ganda Buanindo Kabupaten Kampar - Herli, Irwan; Nurhidayah, Tengku; Siregar, Yusni Ikhwan (Dinamika Lingkungan Indonesia, 2018)
Work as a palm oil mill worker is a job at risk of exposure to noise that exceeds the threshold value. The purpose of this study was to measure the intensity of noise on the occurrence of hearing complaints, psychological disturbances and Noise Induced Hearing Loss (NIHL) on workers and analyze the relationship of worker characteristics; age, length of service, use of Ear Protective Equipment (EPE) and knowledge of hearing complaints, psychological disorders and NIHL disorders. The research approach used in this research is survey method using cross sectional analytic research design with sampling using purposive sampling technique as many as 40 workers. Data were collected by measuring noise intensity, questionnaires and audiometry inspection. Data analysis using univariate and bivariate analyzes were processed using Spearman test. The result of the research shows that there is a considerable noise hazard in the work environment of PT. GBI, while the potential impact experienced by workers due to noise in low risk levels. The relation between factory noise intensity and worker characteristic; age, working period, knowledge and compliance of EPE usage in general have no significant relation to the incidence of hearing complaints, psychological disorders and NIHL disorders in workers, except in the variable level of knowledge with psychological disorders have a significant relationship.